Analisis Persepsi Peserta Didik SMP terhadap Pelajaran Matematika - Nurpadillah, Alya; Afriansyah, Ekasatya Aldila (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to describe students' perceptions of mathematics lessons based on three aspects: understanding, accepting, and evaluating mathematics. This study employed a qualitative descriptive approach involving 33 respondents who were students at SMP Negeri 1 Malangbong. This approach was chosen to obtain an in-depth picture of the phenomenon studied based on students' direct experiences and views. Information was collected through statement forms and semi-structured interviews, which were verified through source and technique triangulation. The results of the statement form analysis indicate that the aspect of understanding mathematics is in the very strong category (83%), the aspect of evaluating mathematics is in the strong category (65%), while the aspect of accepting or absorbing is in the moderate category (56%). The interviews conducted aimed to support these results, where most students stated that they understand mathematical concepts but still have difficulty in applying them and their self-assessment of their abilities tends to be low. Students with strong learning motivation and harmonious relationships with teachers generally have a more positive perception of the learning process. The conclusion of this study indicates that students' perceptions of mathematics lessons are categorized as positive, but need to be strengthened in the acceptance aspect through a more contextual learning approach.